Reference Architectures for the Internet of Things - Weyrich, Michael; Ebert, Christof (IEEE software, 2016)
The Internet of Things (IoT) is about innovative functionality and better productivity by seamlessly connecting devices. But a major threat is the lack of architecture standards for the industrial Internet and connectivity in the IoT. This article reviews recent IoT architecture evolution and what it means for industry projects.